2017
DOI: 10.7589/2016-02-029
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Infection or Exposure to Highly Pathogenic Avian Influenzas in Peridomestic Wildlife on an Affected Poultry Facility

Abstract: We evaluated the potential transmission of avian influenza viruses (AIV) in wildlife species in three settings in association with an outbreak at a poultry facility: 1) small birds and small mammals on a poultry facility that was affected with highly pathogenic AIV (HPAIV) in April 2015; 2) small birds and small mammals on a nearby poultry facility that was unaffected by HPAIV; and 3) small birds, small mammals, and waterfowl in a nearby natural area. We live-captured small birds and small mammals and collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
2
18
2
Order By: Relevance
“…We also did not find evidence that input from wild birds played a role in the outbreak of the EA/NA H5N2 outbreak in Midwestern poultry. Instead, our analysis suggested that once the EA/NA H5N2 lineage entered the poultry production system in the Midwest USA, transmission was driven through poultry production‐related mechanisms because we found close phylogenetic distance among sequences from poultry facilities (Figure ), relatively infrequent estimate of cross‐species transmission (Table ), high estimated proportion of viral diversity that was sampled (Table ), and other surveillance data failed to detect this lineage in reservoir hosts (Grear et al., ; Ip et al., ; Jennelle et al., ; Krauss et al., ). We suggest that the lack of detection in wild birds points to facility biosecurity that was nearly sufficient to reduce the epidemic size, but had just enough failures to produce the observed consequences (50M birds depopulated and over US $3 billion; Greene, ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We also did not find evidence that input from wild birds played a role in the outbreak of the EA/NA H5N2 outbreak in Midwestern poultry. Instead, our analysis suggested that once the EA/NA H5N2 lineage entered the poultry production system in the Midwest USA, transmission was driven through poultry production‐related mechanisms because we found close phylogenetic distance among sequences from poultry facilities (Figure ), relatively infrequent estimate of cross‐species transmission (Table ), high estimated proportion of viral diversity that was sampled (Table ), and other surveillance data failed to detect this lineage in reservoir hosts (Grear et al., ; Ip et al., ; Jennelle et al., ; Krauss et al., ). We suggest that the lack of detection in wild birds points to facility biosecurity that was nearly sufficient to reduce the epidemic size, but had just enough failures to produce the observed consequences (50M birds depopulated and over US $3 billion; Greene, ).…”
Section: Discussionmentioning
confidence: 67%
“…However, we estimated that the poultry sequences sampled a high proportion of viral diversity in all segments (Table ). We cannot rule out that an unobserved reservoir of HPAIVs existed outside the sample associated with Midwest, but other surveillance in wild birds on and near infected poultry facilities detected no HPAIVs in wild birds contemporary to the poultry outbreak (Jennelle et al., ) and limited exposure in wildlife (Grear, Dusek, Walsh, & Hall, ; Shriner et al., ). A further observation from the phylogeny of the Midwestern poultry sequences suggested that transmission was not structured by production type, with egg‐laying chicken and domestic turkey facilities represented within the same viral lineages (Figures , ).…”
Section: Discussionmentioning
confidence: 90%
“…Two recent studies that assessed peridomestic wildlife at poultry facilities that had been affected by HP AIV failed to detect antibody‐positive house sparrows (Grear, Dusek, Walsh, & Hall, ; Shriner, Root, et al., ). In this study, we demonstrate that the majority of exposed birds, including house sparrows, seroconverted following deliberate exposure, which suggests that infection in these birds is likely to lead to production of antibodies, although duration of antibody persistence was not evaluated here.…”
Section: Discussionmentioning
confidence: 99%
“…http://www. vancouverratproject.com/vancouver_rat_project/results Accessed January 21, 2017. have typically been in the wake of outbreaks in rural settings such as poultry barns (Nettles et al, 1985;Shriner et al, 2012;Grear et al, 2016); however, rodents sampled in these studies were negative for IAV (Nettles et al, 1985;Grear et al, 2016).…”
Section: Introductionmentioning
confidence: 94%